Investigation of the Photodynamic Effects of Curcumin Against Candida albicans - Dovigo, Livia N. [UNESP]; Pavarina, Ana Claudia [UNESP]; Ribeiro, Ana Paula D. [UNESP]; Brunetti, Iguatemy Lourenço [UNESP]; Costa, Carlos Alberto de S. [UNESP]; Jacomassi, Denis P.; Bagnato, Vanderlei S.; Kurachi, Cristina (Wiley-Blackwell, 2011)
This study describes the association of curcumin with light emitting diode (LED) for the inactivation of Candida albicans. Suspensions of Candida were treated with nine curcumin concentrations and exposed to LED at different fluences. The protocol that showed the best outcomes for Candida inactivation was selected to evaluate the effect of the preirradiation time (PIT) on photodynamic therapy (PDT) effectiveness, the uptake of curcumin by C. albicans cells and the possible involvement of singlet oxygen in the photodynamic action. Curcumin-mediated PDT was also assessed against biofilms. In addition to the microbiological experiments, similar protocols were tested on a macrophage cell line and the effect was evaluated by Methyltetrazolium assay (MTT) and SEM analysis. The optical properties of curcumin were investigated as a function of illumination fluence. When compared with the control group, a statistically significant reduction in C. albicans viability was observed after PDT (P < 0.05), for both planktonic and biofilm cultures. Photodynamic effect was greatly increased with the presence of curcumin in the surrounding media and the PIT of 20 min improved PDT effectiveness against biofilms. Although PDT was phototoxic to macrophages, the therapy was more effective in inactivating the yeast cell than the defense cell. The spectral changes showed a high photobleaching rate of curcumin.